A note on calculating asymptotic confidence intervals for the adjusted risk difference and number needed to treat in the Cox regression model. (30th July 2013) - Laubender, Ruediger P.; Bender, Ralf
<x xml:space="preserve">Abstract</x> Recently, Laubender and Bender (Stat. Med. 2010; 29: 851–859) applied the average risk difference (RD) approach to estimate adjusted RD and corresponding number needed to treat measures in the Cox proportional hazards model. We calculated standard errors and confidence intervals by using bootstrap techniques. In this paper, we develop asymptotic variance estimates of the adjusted RD measures and corresponding asymptotic confidence intervals within the counting process theory and evaluated them in a simulation study. We illustrate the use of the asymptotic confidence intervals by means of data of the Düsseldorf Obesity Mortality Study. Copyright © 2013 John Wiley & Sons, Ltd.